Does board diversity reduce the probability of financial distress? Evidence from Chinese firms - Ali, Shahid; Ali, Shoukat; Jiang, Junfeng; Hedvicakova, Martina; Murtaza, Ghulam (Frontiers in Psychology, 2022)
This paper empirically investigates the impact of cognitive board diversity in education, expertise, and tenure facets on financial distress likelihood in the emerging economy of China. This study examines how this relationship varies across State-Owned Enterprises (SOEs) and Non-State-Owned Enterprises (NSOEs). Paper argues that the Chinese stock market, as a typical emerging market, is an excellent laboratory for studying the impact of board diversity on the probability of financial distress. Its underdeveloped financial system and inadequate investor protection leave firms unprotected from financial hardship. A sample of 12366 observations from 1374 firms from 2010 to 2018 shows that cognitive diversity qualities are positively linked with Z-score, implying that directors with different educational backgrounds, financial skills, and tenures can assist in reducing the probability of financial distress. Cognitive board diversity reduces the likelihood of financial distress in SOEs and NSOEs. However, tenure diversity is insignificant in all cases. Furthermore, the robustness model "two-step system Generalized Methods of Moments (GMM)" demonstrated a positive association between educational diversity, financial expertise, and financial distress scores. The results have significant implications for researchers, managers, investors, regulators, and policymakers.